Humic acid in the production of ornamental lawn plugs and shading levels in the development of Carpet grass - Watanabe, Beatriz; Tavares, Armando Reis; Costa, João Victor [UNESP]; do Nascimento, Matheus Vinicios Leal [UNESP]; Zabotto, Alessandro Reinaldo [UNESP]; de Godoy, Leandro José Grava [UNESP]; Bôas, Roberto Lyra Villas [UNESP]; dos Santos, Patrick Luan Ferreira [UNESP] (FapUNIFESP (SciELO), 2025)
Abstract The use of biostimulants has been studied as a technology that improves the cultivation of plant species and could therefore be an option for producing turfgrass seedlings. Furthermore, Carpet grass is recommended for semi-shaded locations, however there are few studies that indicate the best shading percentage for the species. Thus, this work aimed to evaluate humic acid in the production of ornamental lawns plugs and shading levels in the development of Carpet grass. The experiment was divided into two parts, the first being the production of seedlings (30 days) of Emerald grass, DiscoveryTM Bermudagrass, Carpet grass and Bahiagrass with application of humic acid. On the second part the development of Carpet grass was evaluated at 4 levels of luminosity (full sun and shading of 30%, 50%, and 80%) in 28 days. The evaluations carried out were: green color index (GCI), normalized difference vegetation index (NDVI), root length and dry mass of the seedlings for the first part. And for the second part: GCI, SPAD (Soil Plant Analysis Development), NDVI, visual aspect, coverage rate, lawn height and dry mass of clippings. It was observed that the use of a humic acid-based biostimulant is recommended in the production of plugs for ornamental lawns, and the best results on Carpet grass, where, the shading level up to 50% for this species is recommended in analyses of up to 28 days. Resumo O uso de bioestimulantes vem sendo estudado como uma tecnologia que melhora o cultivo das espécies vegetais, podendo assim ser opção para produção de mudas de grama. Ainda, a grama São Carlos é recomendada para locais semi-sombreados, entretanto são poucos estudos que indicam a melhor porcentagem de sombreamento da espécie. Assim, esse estudo teve como objetivo avaliar ácido húmico na produção de plugs de gramas ornamentais e níveis de sombreamento no desenvolvimento da grama São Carlos. O experimento foi dividido em duas partes, sendo a primeira a produção de mudas (30 dias) de grama Esmeralda, Bermuda DiscoveryTM, São Carlos e Batatais com aplicação de ácido húmico, na segunda parte foi avaliado o desenvolvimento da grama São Carlos em 4 níveis de luminosidade (pleno sol, sombreamento de 30%, 50% e 80%) em 28 dias. As avaliações realizadas foram: índice de cor verde (ICV), índice de vegetação por diferença normalizada (NDVI), comprimento da raiz e massa seca das mudas para a primeira parte. No segundo estudo: ICV, SPAD (Soil Plant Analysis Development), NDVI, aspecto visual, taxa de cobertura, altura do gramado e massa seca das aparas. Observou-se que O uso de bioestimulante a base de ácido húmico é recomendada na produção de plugs de gramados ornamentais, com destaque para a grama São Carlos, onde, o nível de sombreamento até 50% para essa espécie é recomendado em análises de até 28 dias.